Modulation of Negative Affect Predicts Acceptance of Music Streaming Services, While Personality Does Not - Hilsdorf, Max; Bullerjahn, Claudia (Frontiers in Psychology, 2021)
Music streaming services offer their users numerous ways of choosing and implementing their individual approaches to music listening. Personality, uses of music, and the acceptance of music streaming services can be conceptualized as interdependent. This study investigates whether negative affect modulation strategies explain differences in the acceptance of music streaming services and integrates findings from previous research into a structural equation model. As for measurements, the Big Five Inventory 2 (BFI-2), the Inventory for the Assessment of Activation- and Arousalmodulation through Music (IAAM), and adapted scales from previous research on the Technology Acceptance Model (TAM) were used. A convenience sample of 825 participants (24.3 years, 74% females, 89% students) successfully completed an online questionnaire. 89 percent of the sample reported using music streaming services regularly. The results show that the tendency to modulate negative affect through music is positively inﬂuenced by openness and neuroticism. In turn, the tendency to modulate negative affect through music is shown to increase the perceived usefulness of music streaming services. However, this study failed to replicate the previous findings that openness increases the attitude towards using and that neuroticism decreases the perceived usefulness. This implies that uses of music are more effective than personality traits at predicting the individual acceptance of music streaming services. However, personality can be viewed as a predictor for uses of music. The interwovenness of stable and situational factors of music choices is supported. Music streaming services seem to assist their users in coping with negative affect in everyday life, increasing wellbeing. Music streaming services should expand their personalization features to optimize user experience with respect to individual uses of music.